Acute Cardiotoxicity With Concurrent Trastuzumab and Hypofractionated Radiation Therapy in Breast Cancer Patients - Sayan, Mutlay (Front Oncol, 2019)
Purpose: Radiotherapy for patients with non-metastatic human epidermal growth factor receptor 2 (HER2) positive breast cancer is commonly administered concurrently with adjuvant trastuzumab. However, there is limited data on the use of concurrent trastuzumab and hypofractionated radiotherapy (Hypo-RT), which is now standard of care for the majority of women receiving whole breast irradiation. In this study, we compared acute cardiotoxicity rates in HER2-positive breast cancer patients treated with concurrent trastuzumab and Hypo-RT or conventionally fractionated radiotherapy (Conv-RT). Methods: We performed a review of our institutional database to identify HER2-positive breast cancer patients treated with trastuzumab and Hypo-RT or Conv-RT from 2005 to 2018 who underwent serial cardiac Left Ventricular Ejection Fraction (LVEF) evaluation. Decrease in LVEF was assessed by either echocardiography (ECHO) or multiple gated acquisition (MUGA) scan performed at baseline and every 3 months during trastuzumab therapy. Significant LVEF decline was defined as an absolute decrease in LVEF of ≥10% below the lower limit of normal or ≥16% from baseline value. Results: We identified 41 patients treated with Hypo-RT and 100 patients treated with Conv-RT. Median follow-up was 32 months (range, 13–90 months). Baseline median LVEF was 62% (range, 50–81%) in Hypo-RT group and 64% (range, 51–76%) in Conv-RT group (p = 0.893). Final median LVEF was 60% (range, 50–75%) in both groups. Three patients (7%) in Hypo-RT and five (5%) in Conv-RT group developed significant asymptomatic LVEF decline (p = 0.203). There was no significant difference in mean heart dose in patients who developed significant asymptomatic LVEF decline vs. those who did not in Hypo-RT (p = 0.427) and Conv-RT (p = 0.354) groups. No symptomatic congestive heart failure was reported in either group. Conclusions: The rate of asymptomatic LVEF decline in patients receiving concurrent trastuzumab and Hypo-RT was low (7%) and was similar to the rate observed in patients receiving Conv-RT. Longer follow-up is warranted to assess late cardiotoxicity.